DISCRIMINATION, TAX CONSCIOUSNESS, AND SERVICE QUALITY TOWARDS PERCEPTION OF TAX EMBEZZLEMENT - Indriyani Astuti Nurachman; Catur Martian Fajar; Adi Suparwo (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
Tax fraud is a problem that often occurs in all parts of tax administration, one of which is tax evasion. As a result, the perception of taxpayers is reluctant to pay taxes. This is seen from the low awareness of taxpayers in the Bandung KPP Intermediate. The purpose of this study was to determine the effect of discrimination, awareness of taxpayers and the quality of tax services on the perception of tax evasion. This research uses descriptive verification method with a quantitative approach. The data source used is primary data as a result of distributing questionnaires to taxpayers as many as 100 respondents. Based on the results of the study showed that partially discrimination and awareness of taxpayers have no significant effect on the perception of tax evasion. But the quality of tax services has a significant effect on the perception of tax evasion. Simultaneously discrimination, awareness of taxpayers and the quality of tax services have a significant effect on the perception of tax evasion. The quality of tax services has the most influence on the perception of tax evasion with indicators of accuracy of information. From the results of the research, it is expected that tax officials are always swift and willing to provide clear and understandable information by taxpayers, so that taxpayers feel satisfied with the services provided because it can reduce tax evasion at the Intermediate Tax Office in Bandung. Keywords: Discrimination, taxpayer awareness, tax service quality, perceptions of tax evasion